PENGARUH KOMUNIKASI ORGANISASI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KETERIKATAN KARYAWAN PT. GLOBAL RETAILINDO PRATAMA - Ni Komang Niken Diah Pratiwi,; Putu Suparna, (Journal of Innovation Research and Knowledge, 2025)
Employee engagement is a critical factor in maintaining organizational performance and employee retention, particularly in the retail industry, which is characterized by high work intensity and employee turnover. This study aims to examine the effect of organizational communication and transformational leadership on employee engagement at PT. Global Retailindo Pratama Region Bali. The research employed a quantitative associative approach using a census sampling technique, involving all 40 employees as respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that organizational communication does not have a significant partial effect on employee engagement, although the relationship shows a positive direction. In contrast, transformational leadership has a positive and significant effect on employee engagement and emerges as the dominant variable in the model. Simultaneously, organizational communication and transformational leadership significantly influence employee engagement, explaining 59.7% of its variance. These findings suggest that while communication remains an important organizational function, transformational leadership plays a more decisive role in fostering employee engagement in the retail context. Strengthening transformational leadership practices is therefore essential to enhance employee engagement and reduce turnover